2006
DOI: 10.1590/s1413-70542006000400012
|View full text |Cite
|
Sign up to set email alerts
|

Temperature response of photosynthesis and its interaction with light intensity in sweet orange leaf discs under non-photorespiratory condition

Abstract: This study aimed to evaluate the response of photosynthesis (A), given by photosynthetic O 2 evolution, to increasing temperature from 25 to 50ºC in sweet orange (Citrus sinensis (L.) Osbeck) leaf discs under non-photorespiring conditions. In order to evaluate the response of gross photosynthesis to temperature and the balance between photosynthetic and respiratory activities, respiration (R d ) rates were also measured, i.e. the O 2 uptake in each temperature. In addition, light response curves of photosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 21 publications
1
21
0
5
Order By: Relevance
“…2004). Ribeiro, Machado & de Oliveira (2006) observed a steep increase in respiration under high temperatures in steady‐state conditions, but did not observe a break‐point. As an excess of reductants may be generated under high temperature (Bukhov et al .…”
Section: Discussionmentioning
confidence: 94%
“…2004). Ribeiro, Machado & de Oliveira (2006) observed a steep increase in respiration under high temperatures in steady‐state conditions, but did not observe a break‐point. As an excess of reductants may be generated under high temperature (Bukhov et al .…”
Section: Discussionmentioning
confidence: 94%
“…Considering high temperatures, Guo et al (2006) found a significant reduction in citrus photosynthesis, with impairment of primary photochemistry under 38ºC. Citrus respiration is also affected by temperature, being stimulated in leaf temperatures higher than 35ºC (Ribeiro et al, 2006a). As exposed leaves of field-grown trees commonly face temperatures higher than 35ºC under subtropical conditions , citrus plants have to deal with both low and high temperatures during their life span.…”
Section: Introductionmentioning
confidence: 99%
“…Although high and low temperature effects on citrus physiology have been reported, it is difficult to establish the importance of such physiological responses for plant growth, as most studies have not addressed the morphological or biometric changes caused by sub or supraoptimal temperatures (Guo et al, 2006;Machado et al, 2005;Ribeiro et al, 2006a;2009a;Santos et al, 2011). In addition, most of the available literature reports the physiological responses of tree species to extreme temperature conditions, for instance near to heat damage or freezing (Ahrens and Ingram, 1988;Hoch and Körner, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Ribeiro et al, 10 a temperatura é um dos mais importantes fatores ambientais que influenciam a fisiologia das plantas, sendo a atividade fotossintética especialmente sensível a mudanças de temperatura. A fotossíntese, não somente determina o crescimento e desenvolvimento das plantas através da incorporação de carbono, mas também consiste no passo inicial para a síntese de metabólitos secundários, incluindo os óleos essenciais.…”
Section: Influência Das Condições Ambientais Sobre O Rendimentounclassified